Crédito digital e superendividamento do consumidor - Di Stasi, Mônica (2023)
The objective of this work is to analyze the relation between consumption and credit, and their consequences. Based on bibliographical analysis, jurisprudence and national and foreign regulatory review, uses deductive method to propose a new mechanism for protecting credit consumers. The objective is to minimize their vulnerabilities, especially behavioral, and bring greater balance to relation, preserving the dignity of the human person. It begins with a historical approach to the institutes, until the moment they enter the digital world, giving rise to two important phenomena: consumer indebtedness (healthy and essential for economic growth) and over-indebtedness (negative externality, which affects thousands of people, producing legal, economic, social and psychological effects). It analyzes the major global models of non-trader insolvency - the French and the North American - with the aim of understanding their foundations and modes of action. Afterwards, moves on to the study of Act 14.181/21 and its procedures. Regarding to digital credit, as the specific discipline in Brazil is still in the formulation phase, analyses the OECD and European Union Directives. With the aim of broadening the horizons of this research, it looks to other sciences, especially Economics and Psychology, for explanations that could make human behavior in making intertemporal decisions involving credit and consumption more understandable. Starting from the recognition that people do not always act rationally and tend to maximize their well-being, making clear that their vulnerabilities must be taken care of, it concludes by presenting the suggestion of a new protection instrument to be incorporated into the consumer protection microsystem: a mandatory reflection period, applicable to digital credit contracts, during which their effects are suspended. The idea is to enable people to move away from the offer environment and analyze it based on their needs and possibilities, thereby avoiding the harmful consequences of over-indebtedness.